2019
DOI: 10.1016/j.jsxm.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Tadalafil and α1-Adrenoceptor Antagonists on Spontaneous Seminal Emission and Electrical Field Stimulation-Induced Seminal Vesicle Contraction in Rats

Abstract: Background Although numerous reports have shown that α1-adrenoceptor (α1-AR) antagonists, which are used to treat benign prostatic hyperplasia (BPH), can cause ejaculatory disorders, few studies have investigated whether the phosphodiesterase 5 (PDE5) inhibitor tadalafil has such adverse effects. In this study, we compared the effects of tadalafil and α1-AR antagonists on seminal emission and their mechanisms of action. Aim T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…In our study, the selective α 1D ‐AR antagonist BMY7378 did not affect SSE, suggesting that the use of drugs with a high affinity for α 1A ‐AR in particular caused EjD. These results were supported by previous reports that showed silodosin, a highly selective α 1A ‐AR antagonist, can suppress SSE more strongly than tamsulosin and naftopidil 25 . In addition, silodosin had been shown to cause EjD most frequently compared to other α 1 ‐AR antagonists in clinical trials 9,21 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, the selective α 1D ‐AR antagonist BMY7378 did not affect SSE, suggesting that the use of drugs with a high affinity for α 1A ‐AR in particular caused EjD. These results were supported by previous reports that showed silodosin, a highly selective α 1A ‐AR antagonist, can suppress SSE more strongly than tamsulosin and naftopidil 25 . In addition, silodosin had been shown to cause EjD most frequently compared to other α 1 ‐AR antagonists in clinical trials 9,21 .…”
Section: Discussionsupporting
confidence: 90%
“…These results were supported by previous reports that showed silodosin, a highly selective α 1A -AR antagonist, can suppress SSE more strongly than tamsulosin and naftopidil. 25 In addition, silodosin had been shown to cause EjD most frequently compared to other α 1 -AR antagonists in clinical trials. 9,21 Together, these findings suggested that affinity for the α 1A -AR plays an important role in EjD.…”
Section: Discussionmentioning
confidence: 99%
“…According to these reports, in this study we used tadalafil at 10 mg/kg/day for 30 days. Recently Yoshinaga et al [25] reported that C max values of 68.5 and 460 ng/ml in rats after single oral doses of tadalafil of 2 and 10 mg/kg, respectively are physiologically relevant with the clinical plasma concentration of tadalafil is 95.6 ng/ml when the drug is administered at 5 mg/person (for BPH patients) and 446 ng/ml when it is administered at 40 mg/person (for PAH patients). Since the doses of tadalafil used in current studies are similar to the plasma concentrations in humans being treated for BPH and PAH, the results we showed in the paper partly may explain the protective mechanisms of Tadalafil in BPH patients.…”
Section: Discussionmentioning
confidence: 99%